Characteristics of effective self-management interventions in patients with COPD: individual patient data meta-analysis. Issue 1 (28th April 2016) - Jonkman, Nini H.; Westland, Heleen; Trappenburg, Jaap C.A.; Groenwold, Rolf H.H.; Bischoff, Erik W.M.A.; Bourbeau, Jean; Bucknall, Christine E.; Coultas, David; Effing, Tanja W.; Epton, Michael; Gallefoss, Frode; Garcia-Aymerich, Judith; et al.
It is unknown whether heterogeneity in effects of self-management interventions in patients with chronic obstructive pulmonary disease (COPD) can be explained by differences in programme characteristics. This study aimed to identify which characteristics of COPD self-management interventions are most effective. Systematic search in electronic databases identified randomised trials on self-management interventions conducted between 1985 and 2013. Individual patient data were requested for meta-analysis by generalised mixed effects models. 14 randomised trials were included (67% of eligible), representing 3282 patients (75% of eligible). Univariable analyses showed favourable effects on some outcomes for more planned contacts and longer duration of interventions, interventions with peer contact, without log keeping, without problem solving, and without support allocation. After adjusting for other programme characteristics in multivariable analyses, only the effects of duration on all-cause hospitalisation remained. Each month increase in intervention duration reduced risk of all-cause hospitalisation (time to event hazard ratios 0.98, 95% CI 0.97–0.99; risk ratio (RR) after 6 months follow-up 0.96, 95% CI 0.92–0.99; RR after 12 months follow-up 0.98, 95% CI 0.96–1.00). Our results showed that longer duration of self-management interventions conferred a reduction in all-cause hospitalisations in COPD patients. Other characteristics are not consistently associated with differential effects of self-management interventions across clinically relevant outcomes. Increasing duration of self-management interventions reduces risk of all-cause hospitalisations in patients with COPD http://ow.ly/YVw9E